The Impact of Corporate Social Responsibility, Profitability, Capital Intensity, Size Company and Financial Distress on Tax Aggressivity (Empirical Study of Manufacturing Companies Listed on the IDX in 2017-2019) - Muhammad Abdul Aris; Alvinia Nabila; Dewita Puspawati (Universitas Muhammadiyah Surakarta, 2022)
This study aimed to examine and analyze the impact of corporate social responsibility, profitability, capital intensity, company size, and financial distress on tax aggressiveness. The population in the study was manufacturing companies listed on the IDX in 2017-2019. The measurement of tax aggressiveness used the effective tax ratio. Sampling was purposive sampling and obtained 177 samples with three years of observation. The analysis in this study used the classical assumption and hypothesis test of multiple linear regression analysis with F-test, t-test, and the coefficient of determination processed using the SPSS version 25. The results of this study indicate that the variable of capital intensity does not affect tax aggressiveness. In comparison, the variables of corporate social responsibility, profitability, company size, and financial distress affect tax aggressiveness.